2017
DOI: 10.31768/2312-8852.2017.39(4):291-298
|View full text |Cite
|
Sign up to set email alerts
|

Cd150 and Cd180 Are Involved in Regulation of Transcription Factors Expression in Chronic Lymphocytic Leukemia Cells

Abstract: Background: Sequential stages of B-cell development is stringently coordinated by transcription factors (TFs) network that include B-lineage commitment TFs (Ikaros, Runx1/Cbfb, E2A, and FOXO1), B-lineage maintenance TFs (EBF1 and PAX5) and stage specific set of TFs (IRF4, IRF8, BCL6, BLIMP1). Deregulation of TFs expression and activity is often occurs in malignant B cells. The aim of this study was to evaluate TFs expression in chronic lymphocytic leukemia cells taking into consideration CD150 cell surface exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…3). On the other hand, downregulation of IRF4 after CD150 + CD180 ligation also could affect transcriptional programs in CLL B cells [78]. It appears that cell surface expression of CD150 and CD180 is not profitable for CLL B cells.…”
Section: Cd150 Is a Candidate For Therapeutic Intervention In Leukemimentioning
confidence: 99%
See 1 more Smart Citation
“…3). On the other hand, downregulation of IRF4 after CD150 + CD180 ligation also could affect transcriptional programs in CLL B cells [78]. It appears that cell surface expression of CD150 and CD180 is not profitable for CLL B cells.…”
Section: Cd150 Is a Candidate For Therapeutic Intervention In Leukemimentioning
confidence: 99%
“…CD180 receptor, but not CD40 or BCR could be involved in regulation of CD150 expression in CLL B cells. Ligation of CD180 on CLL B cells leads to increase of CD150 mRNA level that could be explained by CD180-mediated upregulation of EBF1 expression [78]. From the other hand, it was shown that CD40-CD40L interaction alone or together with leukotriene B 4 activates CLL B cells and results in an augmented CD150 cell surface expression [79].…”
Section: Regulation Of Cd150 Expressionmentioning
confidence: 99%
“…According to our previous data CD150 or/and CD180 ligation on CLL B cells ex vivo led to a decrease in IRF4 mRNA expression up to 4 times. At the same time, after CD150 or CD180 ligation the BCL6 mRNA expression level was increased compare to control although CLL B cells were characterized by lower basal BCL6 mRNA expression in both CD150and CD150 + subgroups of CLL [8]. Considering the above, it could be hypothesized that CD150 or/and CD180 mediated inhibition of IL-10 expression by CLL B cells is connected with regulation of BCL6 and IRF4` mRNA expression via CD150 and CD180 signaling pathways.…”
Section: Resultsmentioning
confidence: 92%
“…Our previous data showed that simultaneous activation of CD150 and CD180 cell surface receptors on CLL B cells led to inhibition of main pro-survival Akt and MAPK signaling pathways [7]. Moreover, activation of CD150 and CD180 receptors on CLL B cells led to changes in mRNA expression levels of transcription factors (TFs) that regulate B cells` identity and differentiation (EBF1, IRF4, IRF8, BCL6 and PU.1) [8]. Since both CD150 as adhesion and costimulatory molecule and CD180 as a pattern recognizing receptor could be activated in tumor microenvironment by pattern of common microbial, neo-and autoantigens we tested a hypothesis whether CD150 and CD180-mediated signaling could be directly linked to modification of CLL microenvironment through regulation of cytokines expression and secretion by CLL B cells.…”
mentioning
confidence: 99%
See 1 more Smart Citation